As concepções de trabalho no serviço social e a dimensão política da profissão: uma abordagem marxista - Fiori, Gecira Di (2013)
The current research examines the relation between the conceptions of labor in Social Work and the political dimension of the profession, aiming at contributing to the debates over the qualification and the critical career plan. The leading issue is the centrality of labor in the Social Work qualification process and in researchers discussions of labor and the professional intervention in the current capitalist reality. From the methodological point of view, the research is quali-quantitative, comprehending the bibliographical research in Marxist tradition works and also by classic and contemporary interpreters; the documentary research whose main sources are the menu made available by Evaluative Research of Social Work Curriculum Guidelines Implementation conducted by ABEPSS (2006-2008) and the Proceedings of the XII National Meeting of Social Work Researchers (2010); and the empirical research that compasses open interviews with four social workers with Marxist references in the theoretical and political direction of their profession. It was used content analysis, which confirmed the assumption that the conception of labor in Social Work is not only an indicator of the profession political dimension but also contributes to delimit different career plans. That results into a challenging issue to Social Work which implies the Marxist political dimension valorization in the historical understanding of contradiction between labor and freedom, and therefore proceeding with the discussions related to the centrality of labor in the Social Work qualification and the critical career plan